Astana International Financial Centre – A Legal Enclave in Kazakhstan - BATYRBEKOVA, Diana S.; UKIN, Symbat K.; SAULEN, Nurzhan; SHUNAYEVA, Sylu M.; ZHUSSUPOVA, Guldaray B. (Journal of Advanced Research in Law and Economics; Vol 10 No 5 (2019): JARLE Volume X Issue 5(43) Fall 2019, 2019)
The scientific article considers issues of higher legal force and direct effect of the Constitution of Kazakhstan throughout the territory of Kazakhstan in light of the functioning of the AIFC in the territory of Kazakhstan. The authors believe that the constitutional wording of paragraph 3-1) of Article 2 of the Constitution that a special legal regime in the financial sphere may be established within the city of Nur-Sultan which, in accordance with the constitutional law, may provide for two approaches. The first approach is that the constitutional postulate on the highest legal force and direct effect of the Constitution throughout the Republic (clause 2 of Article 4) is absolute, and accordingly, it is also applied without any reservations within the city of Nur-Sultan, where a special legal regime in the financial sector is established in accordance with constitutional law. The second approach stipulates that the constitutional postulate on the higher legal force and direct effect of the Constitution throughout Kazakhstan may have its own characteristics within the city of Nur-Sultan, where a special legal regime in the financial sphere is established in accordance with constitutional law. The authors adhere to the first approach. In addition, the article also analyses the definition of ‘legal enclave’ and proposes interpretations of this definition.